IoT - development of home automation system - Lee, Keith (Nanyang Technological University, 2024)
This project proposes a platform for Home Automation IoT (Internet of Things) devices with different hardware and IoT protocols. Portable devices such as mobile phone provides user interface to interact with these IoT devices.